Commitment Theory as the Theoretical Framework in Third-Party Reproduction - Z Behjati Ardakani; MM Akhondi; AH Khodaparast; F Ranjbar; M Navabakhsh (JRI, 2023)
Assisted reproductive technology (ART) and third-party reproduction provide the opportunity for infertile couples to have children through different genetic links. This type of treatment has created many challenges for infertile couples. With this treatment, the infertile couple will have a child who is biologically related to the gamete/embryo donor. Accordingly, the transformation that occurs in the structure of traditional families and the concept of parenthood is one of the main consequences and challenges which requires in-depth research. In spite of the successful expansion of infertility treatment and third-party reproduction, there is still no proper social context for implementing third-party infertility treatments in Iran. Therefore, despite the need to use the technology, some couples refuse the treatment unless their confidentiality is preserved. Many couples follow the practice surreptitiously by keeping the donation treatment confidential, to get rid of the existing social stigma and protect their identity, the child and the donor’s identity. Commitment theory as a theoretical strategy is proposed to solve the problems of all parties involved in this type of "social and non-biological" parenting. Commitment theory in the context of third-party reproduction expresses the commitment to the contract accepted by the donor and the recipient of the gamete/embryo, based on which, the recipients consider the resulting child as their own, and are committed to all the related paternal-maternal rights and duties such as "alimony" and "inheritance". On the other hand, the donors undertake to waive all their paternal-maternal rights and duties by donating gamete/embryo.